Mamfe Native Court Constitution (Colonial Letters and the Contact of Knowledges, 1925)
This file contains colonial memoranda on Mamfe native Court Constitution
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Colonial Native Court; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies